2023
DOI: 10.1039/d2sc06665c
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics and analysis of SARS-CoV-2: current status, recent advances, challenges and perspectives

Abstract: The disastrous spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induced serious public healthcare issues and significantly weakened the global economy. Although infecting SARS-CoV-2 will not be as fatal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 483 publications
0
11
0
Order By: Relevance
“…Improving the assay sensitivity of biosensors is of vital importance to detect targets at ultra-trace levels for the early diagnosis of diseases, biomedicine, and food industries. To achieve this goal, target and signal amplification is commonly required. The polymerase chain reaction (PCR) can amplify a specific DNA strand by a factor of 10 6 and be widely considered as the gold standard, however, constrained by thermal cycling .…”
Section: Introductionmentioning
confidence: 99%
“…Improving the assay sensitivity of biosensors is of vital importance to detect targets at ultra-trace levels for the early diagnosis of diseases, biomedicine, and food industries. To achieve this goal, target and signal amplification is commonly required. The polymerase chain reaction (PCR) can amplify a specific DNA strand by a factor of 10 6 and be widely considered as the gold standard, however, constrained by thermal cycling .…”
Section: Introductionmentioning
confidence: 99%
“…36,37 As the epidemic evolves and the virus mutates, the prevention and treatment of SARS-CoV-2 should be further strengthened to improve the accuracy and sensitivity of diagnostic methods. 38,39 Therefore, in this work, selecting SARS-CoV-2 as a proof of concept, we proposed a nonamplified bioscreening approach to identify peptides that can bind to the SARS-CoV-2 S protein with good affinity and specificity. Subsequently, we constructed the antibody-free pLFIA system using the identified peptide as a capture probe and developed a PDA@MnO 2 -based pLFIA with outstanding oxidase-like activity as a colorimetric tag for significant signal enhancement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polydopamine (PDA), possessing chemical and physical properties similar to those of natural melanin, along with strong adhesion and excellent biocompatibility, is considered to be a typical class of artificial melanin materials. In addition, MnO 2 and MnO 2 -related materials exhibit prominent oxidase-like activities, which can catalyze 3,3′,5,5′-tetramethylbenzidine (TMB) oxidation with remarkable on-demand signal enhancement . The catastrophic spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused serious public healthcare problems and severely weakened the global economy. , As the epidemic evolves and the virus mutates, the prevention and treatment of SARS-CoV-2 should be further strengthened to improve the accuracy and sensitivity of diagnostic methods. , Therefore, in this work, selecting SARS-CoV-2 as a proof of concept, we proposed a nonamplified bioscreening approach to identify peptides that can bind to the SARS-CoV-2 S protein with good affinity and specificity. Subsequently, we constructed the antibody-free pLFIA system using the identified peptide as a capture probe and developed a PDA@MnO 2 -based pLFIA with outstanding oxidase-like activity as a colorimetric tag for significant signal enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging aptamers with good binding affinity and specificity provide opportunities for the establishment of detection methods for SARS-CoV-2 spike protein. 13–20 For example, Metternich et al made use of two aptamers targeting SARS-CoV-2 spike protein to develop a fluorescence detection method based on covalent guanine quantum defect chemistry; 15 Luo et al demonstrated the usability of aptamer-functionalized MXene nanosheets as a novel sensor that allowed detection of SARS-CoV-2 spike protein down to 38.9 fg mL −1 ; 17 Xue et al reported an electrochemical method based on aptamer-binding induced multiple hairpin assembly and successfully applied it to detect as low as 9.79 fg mL −1 SARS-CoV-2 spike protein. 20 Although these methods have shown promising feasibility, they still have some limitations.…”
Section: Introductionmentioning
confidence: 99%